Fatty acid methyl esters production from waste catfish fat (pangasius hypothalamus) using barnacle-Zno as a catalyst - Siti Norhafiza, Mohd Khazaai; Nur Farah Wahida, Abdul Wahid Baki; Maniam, Gaanty Pragas; Mohd Hasbi, Ab. Rahim (Science Publishing Corporation, 2018)
The abundance and diverse populations of Barnacle shells catching the intention as a source of calcium oxide catalyst to transesterify waste catfish fat into methyl ester. Calcium oxide supporte d with zinc oxide was prepared by ball milling method at 1:2 ratios, calcined for 3 h at 400 °C. The characterization of catalyst revealed both metals were well integrated into a bimetallic oxide. The optimal condi-tions were found to be: methanol/oil mass ratio, 10:1; catalyst amount, 11 wt% at the reaction temperature, 65°C with 3 h of reaction time achieving 85.7% of methyl ester conversion. Both feedstock and catalyst from waste source have been successfully utilized to produce biodiesel.